Replication stress–induced nuclear hypertrophy alters chromatin topology and impacts cancer cell fitness - Changgon Kim; Semyeong Hong; Soo Hyeon Ma; Joochan Lee; Hee So; Jun Young Kim; Eunbie Shin; Kippeum Lee; Sohee Choi; Juyeon Park; YongKeun Park; You-Me Kim; et al. (Proceedings of the National Academy of Sciences, 2025)
Microscopic examination of biopsy tissues remains essential for cancer diagnosis, despite advancements in sequencing technologies. Alterations in nuclear size or the nuclear-to-cytoplasmic ratio are hallmark features of cancer cells and often correlate with disease progression. However, the mechanisms underlying nuclear size abnormalities and their impact on tumor progression remain unclear. In this study, we demonstrate that nuclear hypertrophy occurs in response to enhanced DNA replication stress, a key characteristic of cancer cells. Increased actin polymerization within the nucleus appears to be the primary mechanism driving nuclear hypertrophy downstream of the ATR-CHEK1 pathway. Replication stress–induced nuclear hypertrophy alters transcriptomic profiles and chromatin topology, while reducing the migratory and metastatic capacity of cancer cells. In addition, nuclear hypertrophy in cancer cells is associated with increased infiltration of antitumor immune cells. Our findings suggest that cell-autonomous effects of nuclear hypertrophy do not promote cellular fitness or aggressive characteristics in cancer cells. This may explain why cells with nuclear hypertrophy are not positively selected and persist as a subpopulation during tumor progression and metastasis. Furthermore, the link between replication stress and nuclear hypertrophy provides insights into why enlarged nuclei are consistently observed in advanced-stage cancers.